2015
DOI: 10.1176/appi.ajp.2015.14050673
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Working Memory Performance in Schizophrenia by Plasma Ratio of Clozapine to N-Desmethylclozapine

Abstract: This hypothesis-driven study confirms that clozapine/NDMC ratio is a strong predictor of working memory performance in patients with schizophrenia. This finding suggests that manipulating the clozapine/NDMC ratio could enhance cognition in patients with schizophrenia treated with clozapine. It also supports the study of procholinergic agents, such as M1 receptor-positive allosteric modulators, to enhance cognition in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 42 publications
5
38
1
Order By: Relevance
“…Working memory performance prediction has become an interesting topic which received considerable attention in recent years ( Rajji et al, 2015 ; Johannesen et al, 2016 ; Tumari and Sudirman, 2016 ). In previous attempts, numerous approaches were proposed to extract reliable features to predict individual WM performance and distinguish the difficulty levels of cognitive tasks, such as alpha power ( Myers et al, 2014 ), absolute power ( Klimesch et al, 2006 ), and wavelet entropy ( Zarjam et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Working memory performance prediction has become an interesting topic which received considerable attention in recent years ( Rajji et al, 2015 ; Johannesen et al, 2016 ; Tumari and Sudirman, 2016 ). In previous attempts, numerous approaches were proposed to extract reliable features to predict individual WM performance and distinguish the difficulty levels of cognitive tasks, such as alpha power ( Myers et al, 2014 ), absolute power ( Klimesch et al, 2006 ), and wavelet entropy ( Zarjam et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RBANS, and TMT were administered within one week following the administration of the PANSS. As done in previous studies ( Kalache et al, 2015 ; Rajji et al, 2015 ), seven main cognitive domains were assessed as follows: (i) immediate recall: RBANS story memory immediate recall (SM-IR); (ii) delayed recall: RBANS story memory delayed recall (SM-DR); (iii) language: RBANS picture naming test; (iv) auditory attention: RBANS digit span; (v) visual attention: TMT-A; (vi) information-processing speed: RBANS digit symbol coding; and (vii) executive functioning: TMT-B. For all measures, raw scores were used for the analysis.…”
Section: Methodsmentioning
confidence: 79%
“…In some patients with a low clozapine/NDMC ratio, however, it is still possible that M 1 receptors are partially activated by NDMC. In line with this possibility, a recent study in clozapine-treated patients demonstrated that the clozapine/NDMC ratio, but not individual clozapine and NDMC concentrations, was significantly and negatively associated with working memory performance after controlling for age, gender, education, and symptom severity (Rajji et al, 2015).…”
Section: Discussionmentioning
confidence: 84%